Sero-prevalence of Hepatitis C virus infection in patients undergoing haemodialysis in Al-Najaf Province - Khalida Abbas Al Kelaby; Qabas Neamah Hadi Al Hajjar; Ghaith Kadhim Al Azam (Journal of the Pakistan Medical Association, 2023)
This study identified the predominance of HCV in patients undergoing haemodialysis and the risk factors related to age, gender, residence and occupation. It was conducted in the haemodialysis centre in Al-Saddar hospital in Al-Najaf province. A total of 193 patients were enrolled. Blood was drawn for testing HCV antibodies using ELISA. A positive result for presence of antibodies confirmed HCV infection. Of 193 patients studied, 43(22.3%) were infected with HCV. The higher frequency of infection was in the age group 31- 50 years (11.4%). The rate of HCV in women was (22.89%), while in men it was (21.81%) which was an insignificant difference. Continue....